The National Renewable Energy Laboratory's Wind for Schools Project in Kansas - Miller, Ruth Douglas; Hopkins, Mark; Brown, Amanda (Kansas State University, 2009)
The National Renewable Energy Laboratory (NREL) began the Wind for Schools (WfS) Project as part of the Wind Powering America (WPA) Program. WfS was started to promote wind energy education among rural school teachers and students, educate college students in wind energy applications, and introduce small-scale wind energy to rural communities. Kansas State University (KSU) and Dr. Ruth Douglas Miller were chosen by NREL to set up a Wind Applications Center (WAC) to lead project development in the state of Kansas. To accomplish the goals of the project, five small wind turbines were erected at rural Kansas schools and one small turbine on KSU property in the first year. An additional five turbines will be erected at rural Kansas Schools in each of the two years following the first year for a total of 15 turbines at rural Kansas schools and one turbine at KSU upon completion of the three year project. To be selected for the project, schools must submit a proposal and satisfy several criteria set forth by NREL. The purpose of this presentation will be to showcase the successes of the WfS project, discuss improvements that can be made, and discuss the future of the WAC at KSU.
Keywords: National Renewable Energy Laboratory; Wind energy; Rural schools; Wind for Schools Project; Kansas; Wind Powering America Program